Implementing Mindfulness in General Life and Organizations. Validation of the Time Flow Mindfulness Questionnaire for Effective Health Management - Petitta, Laura; Sinato, Emanuela; Giannelli, Maria Teresa; Palange, Miriam (Frontiers in Psychology, 2022)
The primary purpose of the current research was to examine the psychometric properties of the Time Flow Mindfulness Questionnaire (TFMQ), a new self-report scale designed to measure cognitive, emotional, bodily, context-related, and action-related distracting inputs experienced by the mind during three different time windows of mindfulness practice (preliminary moments, during-the-practice, after-the-practice). The 42-item scale assesses the following second-order and first-order factors: Practice (preliminary, during), Benefits (short-term, long-term) and Benefits at work. Three studies were conducted. The first study assessed the factor structure and internal consistency on a sample of 141 mindfulness practitioners. Using a two-wave lagged design on a different sample of 46 trainees attending MBSR courses, the second study examined concurrent validity by performing correlations between the TFMQ and Five Facets Mindfulness Questionnaire (FFMQ). The third study (same sample as study 1) examined criterion validity by testing a structural equation model wherein mindfulness practice predicts job burnout, both directly and indirectly through mindfulness benefits at work. All studies relied on anonymous surveys. Our findings suggest that the TFMQ: a) has a factor structure consistent with the hypothesized conceptual dimensions; b) has good concurrent validity as demonstrated by significant correlations with the FFMQ dimensions; and c) consists of mindfulness dimensions that predict job burnout in organizations (i.e., criterion validity). The TFMQ is a valid and reliable mindfulness measure that may help a) practitioners gain awareness of different types of inputs that potentially distract the mind and mindfulness beneficial consequences, and b) organizations implement mindfulness in work-settings.